Tales from shakespeare - Lamb, Charles; Lamb, , Mary (Penguin Books London, 2007)
Celebrated prose retellings of Shakespeare's plays Charles and Mary Lamb have delighted generations of adults as well as children with their famed prose renderings of Shakespeare's originals. Bringing the plays to life in a form that encourages readers to enjoy and explore, Tales from Shakespeare provides an entertaining and informative introduction to the great works while retaining much of Shakespeare's lyricism, phrasing, and rhythm. It is a captivating work of Romantic storytelling as well as the original literary homage to the Bard. For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,700 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators.